Safe operating procedure for administration of Intravenous (bolus) medications - Abu Bakar, Nor’Aishah; Chee, Monica Soon Nyuk; Ng, Siew Luan; Ramli, Darmawan; Jaafar, Suzana; Mohd Husin, Norlaila; Ahmad, Zanita; Awang, Razmiyah; See, Booi Cheng; Esa, Noor Wati; Alias, Mariati; Harun, Noorsiah; et al. (Ministry of Health, 2017)
This guideline will be useful for nurses in the clinical field who need to perform and master in this procedure especially for the privileging process. It not only protects patient and the health facility by lowering the risk of medical errors that may be caused by incompetent healthcare providers but also enhances the reputation and credibility of the health facility and the health care community